2022
DOI: 10.1155/2022/6590557
|View full text |Cite|
|
Sign up to set email alerts
|

Application of AI Information Technology in the Political and Ideological Online Classroom System in the Background of Big Data

Abstract: Political and ideological online teaching is a new thing integrating political and ideological theory teaching and artificial intelligence information technology. In order to effectively improve the quality of political and ideological online teaching, this paper aims to make an in-depth study on the application of artificial intelligence technology in the political and ideological online classroom system under the background of big data. This paper first expounds the overall architecture of the political and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In order to ensure the security of the data, a backup database is used. Due to the use of an external network connection, it is necessary to go through multiple layers of firewalls when connecting the database server and the application server [4]. To ensure the security of the system, the structure diagram of the information education system is shown in Figure 1.…”
Section: Framework Design Of Information Education Systemmentioning
confidence: 99%
“…In order to ensure the security of the data, a backup database is used. Due to the use of an external network connection, it is necessary to go through multiple layers of firewalls when connecting the database server and the application server [4]. To ensure the security of the system, the structure diagram of the information education system is shown in Figure 1.…”
Section: Framework Design Of Information Education Systemmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%